2016
DOI: 10.1519/jsc.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of High-Intensity Eccentric Exercise on Vascular Endothelial Function in Young Men

Abstract: Choi, Y, Akazawa, N, Zempo-Miyaki, A, Ra, S-G, Shiraki, H, Ajisaka, R, and Maeda, S. Acute effect of high-intensity eccentric exercise on vascular endothelial function in young men. J Strength Cond Res 30(8): 2279-2285, 2016-Increased central arterial stiffness is as an independent risk factor for cardiovascular disease. Evidence regarding the effects of high-intensity resistance exercise on vascular endothelial function and central arterial stiffness is conflicting. The purpose of this study was to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…These suggest that the muscle damage induced ECC1 did not affect the changes in baPWV. As described above, previous studies have shown that arterial stiffness increased after eccentric exercise that induced muscle damage (Barnes et al 2010;Burr et al 2015;Choi et al 2016;Lin et al 2017). However, no significant changes in baPWV were evident at any time point after ECC1.…”
Section: Mvc Torquementioning
confidence: 73%
“…These suggest that the muscle damage induced ECC1 did not affect the changes in baPWV. As described above, previous studies have shown that arterial stiffness increased after eccentric exercise that induced muscle damage (Barnes et al 2010;Burr et al 2015;Choi et al 2016;Lin et al 2017). However, no significant changes in baPWV were evident at any time point after ECC1.…”
Section: Mvc Torquementioning
confidence: 73%
“…higher exercise-induced inflammation [3,9,35]. During ECC arm cycling, increased systemic vascular resistance has also been reported [5].…”
Section: Introductionmentioning
confidence: 92%
“…Therefore, there is a need to determine the clinical impact of different modes of exercise (including resistance exercise) on vascular function in woman since (1) young women suffer a disproportionate burden of morbidity and mortality attributable to obesity and have higher morbidity and mortality rates after myocardial infarction compared to men (Maas et al, 2011) and (2) intense exercise which may be experienced particularly in the initial stages of an exercise program may be harmful to blood vessel function. For example, acute high intensity resistance exercise (>80% 1RM) can reduce brachial FMD (Phillips et al, 2011; Choi et al, 2014). In contrast, moderate intensity, aerobic exercise (50–65% VO 2max ) has been shown to improve FMD in lean individuals (Rooks et al, 2011) or reduce FMD in overweight individuals (Harris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%